BLM, STOP DITHERING OVER FEDERAL OIL AND GAS LEASES: WHY THE LEASES MUST BE ISSUED WITHIN 60 DAYS (Utah Environmental Law Review, 2011)
Normal 0 false false false EN-US X-NONE X-NONE /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin-top:0in; mso-para-margin-right:0in; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0in; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Times New Roman","serif"; mso-ascii-font-family:"Times New Roman"; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:"Times New Roman"; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} Over the past decade, the traditional method for leasing federal lands for onshore oil and gas exploration seems to have hit a wall. It has become a matter of practice for wildlife and environmental groups to protest nearly every parcel of land the Bureau of Land Management (BLM) submits to a federal oil and gas lease sale. These protests require a lot of time and effort by the BLM and its staff to review each claim in order to determine which, if any, have any merit. Despite the BLM's practice to carefully review and select lands through its resource management plans and environmental studies, these protests often cause the BLM to attach further stipulations to lands, postpone leasing the lands, or eliminate the lands entirely from the lease sale. What is most troubling is the BLM's recent practice to hold the leases, even after they have been purchased, in order to continue its review of the environmental protests. During this time, the lease payments are held in a sort of limbo where neither the federal government nor the successful bidder has access to the funds. The end result is massive delay in the development of oil and gas, affecting the productivity of oil and gas companies, the revenue of state and federal governments, the jobs in local communities, and diminished access to resources that are vital for our fuel and transportation needs. The problem is that the BLM does not have any authority to hold these leases after they have been purchased at a lease sale. Federal law is clear that the BLM must issue a lease within 60 days following the successful bidder's payment. The BLM is overstepping its authority when it does not issue a lease within 60 days of payment. While the BLM has discretion to lease federal lands before a lease sale, and should use that discretion when the lands will be negatively impacted by oil and gas development, the BLM does not have discretion to withhold or delay the issuance of a lease after the lease sale takes place.